Lipid Abnormalities in Patients With Cushing’s Disease and Its Relationship With Impaired Glucose Metabolism - Sun, Xiaolin; Feng, Ming; Lu, Lin; Zhao, Zixuan; Bao, Xinjie; Deng, Kan; Yao, Yong; Zhu, Huijuan; Wang, Renzhi (Frontiers in Endocrinology, 2021)
Purpose Dyslipidemia has been frequently reported and associated with increased cardiovascular risk in patients with Cushing’s disease (CD). Few studies are available regarding the relationships between lipid abnormalities and other preoperative metabolic comorbidities in CD, and the data on alterations of the lipid profile after surgery is quite variable. We aimed to investigate the associations between hyperlipidemia and other baseline metabolic and hormonal parameters and the impact of surgical remission on lipid metabolism in patients with CD. Methods This retrospective study included 104 patients diagnosed with CD. Baseline hormonal and metabolic parameters were compared between the hyperlipidemia (HLP) group and non-hyperlipidemia (NLP) group, and their relationships with hyperlipidemia at diagnosis were evaluated. Alterations in lipid profiles after surgical remission of CD were evaluated in 65 patients with available follow-up data. Results Upon baseline, logistic regression analysis showed that impaired glucose metabolism (IGM) (OR=4.68, 95%CI:1.38-15.91) and morning cortisol levels (per 10 μg/dl change) (OR=1.81, 95%CI:1.11-2.95) are both independent risk factors of preoperative occurrence of hyperlipidemia in patients with CD. The baseline triglyceride (TG) level was positively correlated with systolic blood pressure (SBP) (r=0.297, p=0.003). Lipid abnormalities had improvement but may persist after surgical remission, and the persisted hyperlipidemia is associated with higher baseline total cholesterol (TC) levels (r=0.505, p=0.033). Conclusions Persistence of post-surgery hyperlipidemia is associated with severe baseline lipid abnormalities. Surgical remission with concomitant control of impaired glucose metabolism at diagnosis may have significant implications for controlling hyperlipidemia and reducing cardiovascular risk in CD.